PREFERENSI ARTHROPODA TERHADAP TUMBUHAN LIAR DI AREA KEBUN TEH AFDELING WONOSARI, SINGOSARI KABUPATEN MALANG - Retno, Raras Setyo (Jurnal Florea, 2014)
The role of insects (arthropods) in human life can affect the yield and quality of agricultural products. Insect pests are insects that regularly or occasionally cause damage that can reduce the yield or quality of agricultural products. The purpose of this study was to determine theÂ preference of arthropods on wild plants, to compare the percentage of interest and time orientation of arthropods on wild plants. This research is a qualitative descriptive that tries to reveal andexplain about the preferences or interests arthro in Poda against wild plants (weeds) Cambodgien Wonosari Tea Garden Area, Singosari Malang. The difference in the percentage interest in insects against wild plants affected by volatile compounds secreted by wild plants. Overall plant containÂ volatile compounds produced by the leaves, flowers or fruit of the wild plants cause differencesÂ insect attraction. Insects itself able to select and respond to volatile compounds from plants that are in nature can be visited.Keywords : insects, arthropods, wild plants.